2018
DOI: 10.14419/ijet.v7i3.7.16264
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Dietary Fat Sources on Performance, Liver Fatty Acid Composition and Meat Cholesterol Content in Broiler

Abstract: A study was conducted to evaluate the effect of feeding diet containing palm oil (PO) and sunflower oil (SO) and their combination on bird performance, liver fatty acid profile and meat cholesterol content of broiler. A total of 144 day-old broiler chicks (Cobb) randomly assigned into four dietary treatments and fed for six weeks. The dietary treatments were T1, 6% PO (control); T2, 4% PO + 2% SO; T3, 2% PO + 4% SO; and T4, 6% SO. The body weight gain increased and feed conversion ratio (FCR) reduced with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…The increment of liver PUFA, linoleic acid (C18:2n-6) and linolenic acid (C18:3n-3) in the liver was similar to that in the serum. Similarly, Khatun et al (38) found higher liver PUFA, linoleic acid (C18:2n-6) and linolenic acid (C18:3n-3) in broiler chickens fed SBO compared to palm oil. Despite SBO contributing high USFA to the diet, the lack of difference in liver USFA was contributed by the higher values of liver palmitoleic acid (C16:1) and oleic acid (C18:1) in palm oils and PKO and the higher values of liver stearic acid (C18:0) in SBO that balanced the USFA.…”
Section: Fatty Acid Profiles Of Livermentioning
confidence: 84%
See 2 more Smart Citations
“…The increment of liver PUFA, linoleic acid (C18:2n-6) and linolenic acid (C18:3n-3) in the liver was similar to that in the serum. Similarly, Khatun et al (38) found higher liver PUFA, linoleic acid (C18:2n-6) and linolenic acid (C18:3n-3) in broiler chickens fed SBO compared to palm oil. Despite SBO contributing high USFA to the diet, the lack of difference in liver USFA was contributed by the higher values of liver palmitoleic acid (C16:1) and oleic acid (C18:1) in palm oils and PKO and the higher values of liver stearic acid (C18:0) in SBO that balanced the USFA.…”
Section: Fatty Acid Profiles Of Livermentioning
confidence: 84%
“…The lack of difference in the palmitic acid (C16:0) in the liver was similar to that in the serum. However, Khatun et al ( 38 ) found higher liver SFA and palmitic acid (C16:0) in broiler chickens fed palm oil compared to SBO. The fatty acids supplied by dietary oil influence the fatty acid deposition in the liver tissue of broiler chickens ( 9 , 38 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation